As Manchas Autoritárias do Processo Penal Brasileiro: Quem (Bar)ganha com o Engodo Inquisitório? - GOUVEIA FILHO, Eduardo Correia (Universidade Federal do Pará, 2018)
The present dissertation holds as objective to unveil the degree of authoritarianism and how inquisitorial it is within institutes that adopt bargaining, three in particular: confession as a generic mitigating circumstance to the sentence, plea bargain and penal transaction. A muchneeded look of the past was carried out, focusing on the inquisitorial penal system, so as to pinpoint which features of that system remain, to this day, present in the current Brazilian penal process. Certainly, the use of the researched institutes outlines relevant closeness to that historical period, marked by a high degree of authoritarianism and disregard towards human dignity. In the second part of the study, historical analysis was used to illustrate how the authoritarianism inherent to the Brazilian penal process was born during Brazil’s colonial period, when slavery was lawful. From the examination of certain legal documents from that time, as for instance: the constitution of 1824, the Criminal Code of 1830 and the Code of Criminal Process of 1832, authoritarianism is evident in criminal legislation, which certainly came to be accepted by the Brazilian citizenry, a society that allows, for instance, the presence of institutions that adopt bargaining, known for being violators of fundamental rights and extremely wicked towards the imputed party. In the study’s last part, garantism was selected as theoretical framework, for it consists of a democratic theory, which abides by criteria of rationality and which aims for the restraint of punitive power, being therefore a checks and balances on the punitive spree experimented with in the country, which breaches, in many ways, the constitutional commandments of the Carta Magna of 1988, given that the only model of criminal law feasible in a democratic state is that of minimum penal law.